Multilayer Films Electrodes Consisted of Cashew Gum and Polyaniline Assembled by the Layer-by-Layer Technique: Electrochemical Characterization and Its Use for Dopamine Determination - Sergio Bitencourt Araújo Barros; Cleide Maria da Silva Leite; Ana Cristina Facundo de Brito; José Ribeiro Dos Santos Júnior; Valtencir Zucolotto; Carla Eiras (International Journal of Analytical Chemistry)
We take advantage of polyelectrolyte feature exhibited by natural cashew gum (Anacardium occidentale L.) (CG), found in northeast Brazil, to employ it in the formation of electroactive nanocomposites prepared by layer-by-layer (LbL) technique. We used polyaniline unmodified (PANI) or modified with phosphonic acid (PA), PANI-PA as cationic polyelectrolyte. On the other hand, the CG or polyvinyl sulfonic (PVS) acids were used as anionic polyelectrolytes. The films were prepared with PANI or PANI-PA intercalated with CG or with PVS alternately resulting in four films with different sequences: PANI/CG PANI-PA/CG, PANI/PVS and PANI-PA/PVS, respectively. Analysis by cyclic voltammetry (CV) of the films showed that the presence of gum increases the stability of the films in acidic medium. The performance of the modified electrode of PANI-PA/CG was evaluated in electro analytical determination of dopamine (DA). The tests showed great sensitivity of the film for this analyte that was detected at 10−5 mol L−1.